Shape optimization of the corrugated composite bipolar plate (CCBP) for vanadium redox flow batteries (VRFBs). (15th December 2016) - Choe, Jaeheon; Kim, Jinwhan; Lee, Dai Gil
Abstract: To improve the performance of the vanadium redox flow battery (VRFB), energy losses such as pumping and ohmic losses must be reduced. Such losses occur most at the carbon felt electrode because the highly viscous electrolyte cannot circulate easily through it, and the low fiber content of the carbon felt increases the electrical resistance. Therefore, these losses should be minimized to increase the efficiency of the VRFB. The corrugated composite bipolar plate (CCBP) can reduce these losses, as verified in a previous study. However, because the operating conditions vary, a clarification for these conditions is required for the optimal shape of the corrugation of the CCBP. In this study, the shape optimization of the CCBP was performed, considering the operating condition of the VRFBs. Both the pumping and ohmic losses were calculated and compared for each operating condition, and both an optimal operating condition and a design were determined. Additionally, the contact between the deformed electrode and bipolar plate, as affected by the shape of the corrugation, was investigated by finite element analysis (FEA). Finally, the deformation of the CCBP was calculated by FEA to prevent the flattening of the corrugations when the CCBP is applied to an actual-size stack.